Bibliografia regionalna województwa kujawsko-pomorskiego opracowywana w Wojewódzkiej Bibliotece Publicznej - Książnicy Kopernikańskiej w Toruniu -dokonania, przemiany, dzień dzisiejszy = Regional bibliography of the Kuyavian-Pomeranian Regioncompiled in the Provincial Public Library - the Copernicus Library in Toruń - achievements,transformations and present day - Kozłowska, Monika (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Regional bibliography of the Kuyavian-Pomeranian Region, compiled since 1995 by the Provincial Public Library - the Copernicus Library in Toruń registers literature concerning the Toruń-Włocławek region, which consists of the followingdistricts: Aleksandrowski, Brodnicki, Chełmiński, Golubsko-dobrzyński, Grudziądzki, Lipnowski, Radziejowski, Rypiński, Toruński, Wąbrzeski and Włocławski District. The bibliographic database should be described as a regional subject-related bibliography, containing some elements of authors bibliography.The scope of the bibliography is comprehensive, covering literature on science,art and history of the region, cultural, economic and social life, demographic andgeographical issues, and environmental protection. The bibliographic material covers the years 1995-1996 and 1999-2020 and is continuously updated in the Prolib system, using the National Library Descriptors. The bibliography, which is made available online in the MAK WWW module, OPAC WWW and the INTEGRO catalogue, serves the dissemination of knowledge about the region, meets the diverse educational and information needs of a wide spectrum of recipients,and is the fruit of 26 years of systematic work by several teams of bibliographers.
Keywords: bibliografia regionalna; Wojewódzka Biblioteka Publiczna - Książnica Kopernikańska w Toruniu; biblioteki publiczne; województwo kujawsko-pomorskie; Toruń; regional bibliography; the Provincial Public Library - the Copernicus Library in Toruń; public libraries; the Kuyavian-Pomeranian Region